Understanding (the lack of) space in Psalm 47:6 in light of its neighbouring Psalms : a spatial reading of Psalms 46-48 - Schader, Jo-Mari (Old Testament Essays, 2010)
Psalm 47 is investigated intertextually with Psalms 46 and 48 in terms of their representation of space to determine to where Yahweh ascends in Psalm 47:6. An overview is also given of the theory of Critical Spatiality as well as an overview of the temple as the navel of the Ancient Near Eastern cosmology and spatial orientation. The spatial correlations of Psalm 46-48, i.e. all three's emphasis on the temple and surroundings, will then aid the interpreter in identifying the space in which Psalm 47 plays off. It is also indicated that Psalms 46-48 can be read as a trilogy as they share the same themes and use the same kind of language.
free